Applying Cooperative Learning STAD Model to Improve Students' Reading Comprehension - Ikram Senen; Ashadi; Marseilles Tianusa; Azhari (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Background of the problem: Reading comprehension is a fundamental skill in learning, yet many students have difficulty in mastering it. Conventional learning methods are often less effective in increasing student engagement, so innovative learning models are needed. Purpose: To examine the effectiveness of STAD learning model in improving students' reading comprehension in grade VII at junior school South Halmahera. Method: This study used pre-experiment method with one-group pre-test and post-test design. The research sample consisted of 30 students, who were selected using cluster sampling techniques. Data was collected through reading comprehension tests before and after the application of the STAD model. Data analysis was conducted using t-test to measure the significance of differences in pre-test and post-test results. Result: The pre-test mean score was 55.30, while the post-test mean score increased to 77.40. The t-test result (19.55) was greater than the t-table (1.699) at a significant level of 0.05 with a degree of freedom (df) of 29. This shows that there is a significant increase in reading comprehension after the application of the STAD model. Implication: The results of this study indicate that the STAD learning model can be used as an effective strategy to improve students' reading comprehension. Therefore, it is recommended for educators to apply this model in learning to improve student learning outcomes, as well as develop further research to see its effectiveness in other subjects.